Split/Reduced Liver Transplantation "IMSS": The First Two Cases and Literature Overview - Pierre Jean Aurelus; Hermilo De La Cruz Yáñez; Alfonso Yamamoto Nagano; Nicolás Fernández Mezo; Jacques Baulieux (Archives of Organ Transplantation - Peertechz Publications, 2017)
Introduction: The term Split/Liver Transplantation involved the ex vivo division of an adult cadaver liver into a pediatric allograft and a remnant adult allograft. The efforts were an attempt to satisfy an increasing demand for pediatric cadaver allografts that had resulted in prolonged waiting periods and a wait-list mortality of approximately 50% at major pediatric referral centers. The main of this work is given to know our experience in two different cases and encouraged at the adult surgeons to confide and accept the right allograft of this technique for an adult patient. Cases: We performed two reduced procedures by the split liver technique. The first case was a  procurement of a male donor of 33 years' old with diagnosis of cerebral death due to aneurysm rupture, and the recipient was a five years' old girl with the diagnosis of biliary atresia. For the second case, we had a male donor of 8 years' old with diagnosis of cerebral death secondary to arteriovenous malformation and the recipient was a 2.9 year´s old girl, with biliary atresia. Conclusion: There are no differences in complications between split in cadaveric donor to living liver donor. However for a good outcome, it is important to have a good donor like it is for a good recipient. In our center, the split liver transplantation is uncommon and there is a clear need for better training of surgeons and for improved sharing of information about this needed procedure.